Factorial Analysis on Bacillus Sp. Removal Using Garlic Solution - N., Zainol; Siti Rahmah, Rahim (Universiti Malaysia Pahang, 2017)
Biofilm is a microbial derived sessile community characterized by cells that are irreversibly attached to a substratum or interface to each other, embedded in a matrix of extracellular polymeric substances that they have produced. Many different microbes can be found in biofilm such as Bacillus sp., Listeria monocytogenes, Staphylococcus sp., Escherichia coli and many more. Bacillus sp. was used as biofilm model in this study. The purpose of this study is to determine the most affecting factors in Bacillus sp removal. Garlic solution was used to remove Bacillus sp. In this study, garlic solution was prepared by crushing the garlic and mixed it with water. Bacillus sp. was mixed with nutrient broth before it was incubated. Then, the garlic solution was added into Bacillus sp. mixture and mixed well. The mixture then was spread on nutrient agar. The Bacillus sp. weight on agar plate was measured by using dry weight measurement method. The selected factors were ratio of water to garlic (W/G) (1:1 and 1:5), ratio of garlic solution to Bacillu sp. (GS/B) (1:1 and 1:3), agitation speed (50 –100 rpm) and reaction time between Bacillus sp. and garlic (12-24 hours). Design Expert software (Version 7) was used to construct experimental table where all the factors were randomized. The most contributing factor and interaction between the factors was analyzed via two level factorial analysis by using the same software. The results showed that the most significant factors were GS/B and agitation speed, while for the interaction effect was between W/G and GS/B. The Bacillus sp. removal best condition was determined at W/G at 1:1, GS/B at 1:3, agitation speed at 50 rpm and reaction time at 12 hours. The result of the best condition was 88.46% of Bacillus sp. removal.